Combining morphological and molecular data to identify Padina seaweed samples collected from Hon Thom, Phu Quoc in Vietnam - Huynh Thi , Thu Hue; Vu, Dinh Phong; Nguyen Thi , Bich Ngoc; Nguyen Thi, Thanh Xuan; Do Thi , Thanh Trung; Dam , Duc Tien; Thanh, Le Tat (Academia Journal of Biology, 2024)
The Padina genus has 75 species of which 54 species are classification recognized. The Padina genus has been used as nutritional food that supplies vitamins, proteins, and carotenoids by humans for a long time. Recently, several drugs and dietary supplements containing active components extracted from Padina have been commercially developed. Species of the Padina genus are quietly morphologically similar. Almost all previous studies of the Padina genus used the morphological identification method. This study presents the results of correlation analysis between morphological characteristics and the rbcL marker in the identification of Padina seaweed samples collected at Hon Thom, Phu Quoc, Kien Giang province (HTO), Vietnam. The phylogenetic tree and genetic distance between HTO with references showed the samples belonging to Padina australis. Thus, identification methods based on genetic markers and morphology on HTO seaweed samples were consistent.